Kualitas Papan Semen dari Partikel Serutan Pensil dengan Berbagai Rasio Semen dan Partikel - Desi Natarina Sembiring; Luthfi Hakim; Tito Sucipto (Program studi Kehutanan USU, 2015)
Cement-Bonded Particleboard made of pencil shaving industry waste has not developed in Indonesian. The main objective of this research was to evaluate the physical and mechanical properties of cement bonded from pencil shavings particles and determine the optimum cement-to-particle ratio. The treatment of cement/particle ratio were 90:10; 85:15; 80:20 and 75:25. Methods of this research were two steps curing. The first step was air curing using cold press for ±4 days and continued of second step was oven curing at 80̊ C for 24 hours. The result of the research showed that cement-bonded particleboard produced density value around 0,73-1,13 g/cm3, moisture content 8,37-12,16%, water absorption on immersion 2 hours and 24 hours around 23,78-43,48% and 27,33-51,90%, thickness swelling on immersion 2 hours and 24 hours around 0,79-1,82% and 1,39-2,89%, modulus of elasticity around 114,21-880,17 kg/cm2, modulus of rupture around 7,32-18,52 kg/cm2 and internal bond around 0,88- 1,56 kg/cm2. The effect of cement/particle ratio on the research showed that 80:20 is very good compared from 90:10; 85:15 and 75:25.Key words: cement-bonded particleboard, pencil shavings particles, cement-to-particle ratio.